Effect of etodolac hydrazone, a new compound synthesised from etodolac, on spermatozoon quality, testicular lipid peroxidation, apoptosis and spermatozoon DNA integrity - SÜZGÜN, PELİN; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (WILEY, 2016)
The aim of this study was to investigate the effect of etodolac hydrazone (EH), a new compound synthesised from etodolac, on spermatozoon quality, testicular lipid peroxidation, apoptosis and spermatozoon DNA integrity in rats. Group 1 (n=8) received 1ml dimethyl sulfoxide (DMSO) daily (Control); group 2 (n=8) was treated with 5mgkg(-1)day(-1) EH, dissolved in 1ml DMSO (EH-5); and group 3 (n=8) was treated with 10 mg kg(-1)day(-1) EH, dissolved in 1ml DMSO (EH-10). All administrations were performed by gavage and maintained for 8weeks. Both doses of EH administration caused significant decreases in absolute and relative weights of testis, whole epididymis, right cauda epididymis, and spermatozoon motility, spermatozoon count in comparison with the control group. Only 10mgkg(-1)day(-1) EH administration caused significant decreases in absolute and relative weights of seminal vesicles and serum testosterone level, and significant increases in testicular lipid peroxidation level, and numbers of TUNEL+ apoptotic germ cells and spermatozoa with damaged DNA along with some histopathological damages when compared to the control group. However, body and ventral prostate weight, and testicular antioxidant markers (glutathione, glutathione-peroxidase and catalase), were unaffected significantly by both doses of EH administration. In conclusion, two different doses of EH, in particular its high dose, damage to testicular spermatogenic cells and spermatozoon DNA and, it decreases spermatozoon motility, count and testosterone level in healthy rats.
Keywords: Apoptosis; DNA integrity; etodolac hydrazone; oxidative stress; spermatozoon; IN-VITRO; OXIDATIVE STRESS; CYCLOOXYGENASE-2 INHIBITOR; ANTIINFLAMMATORY DRUGS; ACETYLSALICYLIC-ACID; SCAVENGING ACTIVITY; HYDROGEN-PEROXIDE; ASPIRIN; INDOMETHACIN; RATS